Public Finance and National Accounts in the European Context - Miranda Sarmento, Joaquim (Financial and Monetary Policy Studies,, 2018)
This book offers an essential guide to Public Finance and National Accounts in the context of the European Union. Since the creation of the Eurozone, fiscal policy has been at the heart of economic (but also political/media) discussions in the EU. From the Stability and Growth Pact (1997) to the more recent Fiscal Treaty, EU and Eurozone, countries have been subject to various fiscal rules. The importance of these rules, and of the subsequent procedures that every Eurozone country has to adhere to, is unquestionable. The book provides the reader with an in-depth understanding of the complex EU rules concerning fiscal policy, breaking down the corresponding legal texts into simple and accessible language. It has a broad interdisciplinary appeal, and scholars and practitioners whose work involves these areas will find it of particular interest. .